Psychosocial Suffering and Sexuality in the Context of Covid-19 and Attacks on Human Rights - Vera Silvia Facciolla Paiva; Marcos Roberto Vieira Garcia (Estudos e Pesquisas em Psicologia, 2022)
Fragments of a "pandemic life" collected in prevention projects in outer city and school peripherical territories in São Paulo introduces this article. The impact of the loss of close people to COVID-19, the spread of false information about prevention and care, and the disorganization of daily life emerged from our sustained interaction with young people. Inequality and unemployment were growing before the pandemic, as was the number of mental health events. By co-producing and promoting integrality in prevention with young people, we have followed the social and community response to the syndemic in the context of online schools and school life under the impact of a decade of attacks on sex education. Sexuality, the theme that gave rise to most prevention projects, was challenging to address. Differently from the AIDS responses, community-territorial identities mobilized "untested feasibilities" for this social and health emergency by associating "resistance" to governmental negligence, violation, and the attack on human rights. Globally, this attack questions human rights universality and indivisibility, using sexuality to reinterpret its emancipatory sense of solidarity in difference. The notion of "psychosocial suffering" allows to deal with the excess of individualization and medicalization of suffering experiences structured by inequalities in this long-lasting context.